2012
DOI: 10.1002/term.495
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells improve the osteogenic capabilities of mineralized agarose gels in a rat full-thickness cranial defect model

Abstract: The authors previously created HAp or CaCO(3) formed on or in agarose gels (HAp and CaCO(3) gels, respectively) as biocompatible and biodegradable bone graft materials. However, these gels have limitations for bone regeneration. Mesenchymal stromal cells (MSCs) have osteogenic potential and are considered useful for bone tissue engineering. The purpose of this study was to clarify the osteogenic abilities of MSCs loaded in HAp or CaCO(3) gels (MSC/HAp and MSC/CaCO(3) gels, respectively) using a rat cranial def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…We previously demonstrated that HA/agarose and CaCO 3 /agarose might be suitable as bone graft substitutes in various in vivo bone defect models [4,9,10,11]. However, we also reported that they had limitations for repair of defects in a critical bone defect model, although these limitations could be overcome by loading MSCs onto the gels [12]. The in vitro data from the present study revealed that MSCs easily attached and proliferated on both HA/agarose and CaCO 3 /agarose and, importantly, the attachment/proliferation of ostegenically differentiated MSCs was clearly observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that HA/agarose and CaCO 3 /agarose might be suitable as bone graft substitutes in various in vivo bone defect models [4,9,10,11]. However, we also reported that they had limitations for repair of defects in a critical bone defect model, although these limitations could be overcome by loading MSCs onto the gels [12]. The in vitro data from the present study revealed that MSCs easily attached and proliferated on both HA/agarose and CaCO 3 /agarose and, importantly, the attachment/proliferation of ostegenically differentiated MSCs was clearly observed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the cellular proliferation with high osteogenic capability occurred smoothly on both mineralized gels. We therefore consider the cellular activity observed on the HA/agarose and CaCO 3 /agarose gels as fundamental responses to the loading of MSCs, which is apparently necessary for the successful repair of critical bone defects [12]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be directed to do so in vitro and when implanted in bone can also facilitate bone formation. In fact, several studies have shown that MSCs can be employed to regenerate craniofacial bone in animal studies, supporting the potential of stem-cell-based therapy for bone repair [1][2][3][4][5]. However, there are potential limitations to the use of autologous MSCs in bone repair in humans because most preparatory protocols require the extensive expansion of MSC populations in vitro using animal-derived or recombinant growth factors as well as modulators of transcription and cell survival.…”
mentioning
confidence: 99%